Деформація мотиваційних чинників у сфері праці як передумова формування міграційних настроїв вітчизняних працівників - Семикіна, М. В.; Мельнік, А. В.; Кабай, В. О.; Semikina, M.; Melnik, A.; Kabai, V. (My University, 2017)
Статтю присвячено визначенню ролі пріоритетних мотиваційних чинників у зміні ціннісних орієнтирів вітчизняних працівників та їх поведінки на ринку праці. Систематизовано наукові підходи до розуміння сутності мотивації праці. Розкрито зміст мотиваційних чинників, класифіковано їх види. Проаналізовано результати мотиваційного моніторингу з позицій вияву пріоритетних мотиваційних чинників у сфері праці України. Здійснено економіко-статистичний аналіз, що засвідчив деформації та протиріччя в оплаті праці, які зменшують цінність праці в Україні, зумовлюють поширення міграційних настроїв cеред вітчизняних працівників, призводять до відтоку кваліфікованих фахівців та робітників за межі країни. Introduction. The realities of today reflect the profound contradiction between the declared goals of Ukraine's economic and innovative development and the depreciation of the aspirations of most domestic workers to work effectively within their country, accompanied by social apathy and the spread of migratory sentiment. The phenomenon of loss of the former attitude of the population towards work in the native country as a value has become a consequence of the long-term deformation of motivational factors, in particular the inadequate assessment of labour efforts, which predetermines the spread of poverty among working people. Purpose. The purpose of the article is to reveal the essence of motivational factors in the workplace, the main causes of deformation of their influence on employee behaviour and value orientations. Methods. In order to achieve this goal, general scientific and special research methods are used, in particular: dialectical, logical analysis - to reveal the essence of motivation and motivational factors in the field of work; classification method - to systematize motivational factors according to certain classification criteria; the method of economic-statistical analysis, sociological analysis - to study the priority motivational factors, the features of deformations in their manifestations and consequences for workers' behavior, their migratory sentiment. Results. The results of our study have shown that the labour behaviour of workers is influenced by a multitude of motivational factors that differ in content and levels of influence. In the context of a systemic crisis and a decline in living standards, payroll plays a key role among motivational factors in Ukraine. At the same time, its motivational functions have become deformed, which predetermines the phenomenon of the spread of poverty among the working population, the weakening of the general influence of motivational factors, the destruction of value orientations in the field of labour and the strengthening of migration sentiment. Originality. Proposed author's version of the interpretation of the essence of motivation of labour as a multilevel and multifactorial process. The classification of motivational factors is developed, which details their types depending on the content and levels of influence. The results of motivational monitoring from the standpoint of the appearance of priority motivational factors in the Ukrainian labour market are analysed. Economic and statistical analysis has been carried out, which has shown warpage and controversy in wages that reduce the value of labour in Ukraine, lead to the spread of migratory sentiment among domestic workers, lead to the outflow of skilled workers and workers outside the country. Conclusion. The relatively low level of income from labour, which is scant in the average Ukrainian worker compared to the income of workers in the European Union, causes the limited realization of vital social needs - healthy and balanced nutrition, access to high-quality health care services, quality education, the purchase of decent housing, ensuring professional self-development, healthy leisure, etc. Preserving such a situation can not only worsen the quality of human capital, which will significantly impede the processes of adapting the Ukrainian economy to the requirements of the EU and the movement towards European integration. The prospects for qualitative changes in the motivational system are linked primarily to the rejection of the economic model that Ukraine inherited from the USSR and is based on the use of cheap labour. In our opinion, due to the modernization of enterprises, the increase of the technological and technological level of production, the increase of the level of automation and mechanization of workplaces, rational resource conservation, stimulation, the quality change of the motivational factors and the transition to an innovative model of the economy focused on the use of highly paid work by skilled specialists and workers can be achieved. effective employment at domestic enterprises.
Deformation of motivation factors in the labor sphere as a preliminary formation of migration settles of domestic employees
Keywords: мотивація; мотиваційні чинники; євроінтеграція; деформації; оплата праці; ціннісні орієнтири; міграційна поведінка; motivation; motivational factors; euro integration; deformations; labor remuneration; value orientations; migration behavior